FROM CULTURE SHOCK TO CROSS-CULTURAL UNDERSTANDING IN READING COMPREHENSION: A RECEPTION STUDY OF FIFTH-SEMESTER EFL STUDENTS AT FTIK UIN DATOKARAMA PALU ON STEINBECK’S “THE PEARL” - Andi Muhammad Dakhalan; Ming Pong (Lingeduca: Journal of Language and Education Studies, 2025)
Reading comprehension in EFL teacher education is increasingly framed as an ability to interpret texts critically, engage ethically with difference, and negotiate meaning across cultures. Yet, culturally distant literary texts often provoke affective disruption and moral discomfort that students may label as "culture shock". This qualitative reception study examines how culture shock, elicited through John Steinbeck’s novella The Pearl, became a generative starting point for cross-cultural understanding among ten fifth-semester EFL student-teachers at FTIK UIN Datokarama Palu. Data were collected from reflective reading journals written after each reading segment and a follow-up focus group discussion. The analysis applied an inductive thematic approach to trace recurring shock triggers, interpretive moves, and pedagogical implications. Four interrelated themes emerged: (1) shock at structural injustice and institutional betrayal, (2) shock around gendered violence and patriarchal constraints, (3) shock at materialism and the moral economy of wealth, and (4) movement toward cross-cultural understanding through perspective-taking, value negotiation, and critical comparison with local socio-religious frames. The findings suggest that structured reader-response tasks, especially reflective journals, help student-teachers transform initial emotional resistance into critical, dialogic interpretations that support intercultural reading competence. This study contributes (1) a context-sensitive model of how readers move from culture shock to cross-cultural understanding in an Islamic EFL teacher-education setting and (2) task-level design principles (journal prompts and discussion moves) that instructors can use to evidence and support that movement.